5(2x-3)+6=43-3x

Simple and best practice solution for 5(2x-3)+6=43-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-3)+6=43-3x equation:


Simplifying
5(2x + -3) + 6 = 43 + -3x

Reorder the terms:
5(-3 + 2x) + 6 = 43 + -3x
(-3 * 5 + 2x * 5) + 6 = 43 + -3x
(-15 + 10x) + 6 = 43 + -3x

Reorder the terms:
-15 + 6 + 10x = 43 + -3x

Combine like terms: -15 + 6 = -9
-9 + 10x = 43 + -3x

Solving
-9 + 10x = 43 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-9 + 10x + 3x = 43 + -3x + 3x

Combine like terms: 10x + 3x = 13x
-9 + 13x = 43 + -3x + 3x

Combine like terms: -3x + 3x = 0
-9 + 13x = 43 + 0
-9 + 13x = 43

Add '9' to each side of the equation.
-9 + 9 + 13x = 43 + 9

Combine like terms: -9 + 9 = 0
0 + 13x = 43 + 9
13x = 43 + 9

Combine like terms: 43 + 9 = 52
13x = 52

Divide each side by '13'.
x = 4

Simplifying
x = 4

See similar equations:

| 8+12x=15x-19 | | 2c+5=3c+7 | | 67-5x=9x+7 | | 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 | | 4x-2=11x-43 | | 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 | | 2x^2-11x-24=0 | | 2(x+3)-3=8-2x | | -21-9x=-32-9x | | 114-3x=24x+18 | | 8-7x=93-42x | | 7,000,000a=10 | | -8b-10=-7-6b | | -2(7w-5)+4w=2(w+2) | | 48x^2=0 | | -4-5x=8-4x | | 81+5y=-4y | | 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) |

Equations solver categories